P219 Responding to the LGV epidemic: are the right patients being tested for LGV?. (30th June 2016) - Were, John; Simms, Ian; Hughes, Gwenda; Field, Nigel
Abstract : Background: UK national guidelines will recommend that samples from all Chlamydia trachomatis (CT)-positive men who have sex with men (MSM) with proctitis and all asymptomatic CT-positive MSM with HIV should be tested for Lymphogranuloma venereum (LGV). Aim: To investigate case characteristics and test outcomes of samples referred to the Sexually Transmitted Bacterial Reference Unit (STBRU) for LGV testing. Methods: STBRU and GUMCADv2 data for 2014 in England were matched. Test numbers and outcomes for patients in different risk categories were compared to understand targeting of LGV testing. Results: In 2014, 3, 782 CT samples were tested for LGV, and 2, 426 (64%) were matched to GUMCADv2. MSM accounted for 77% (1876/2426), heterosexual men 7% (178/2426) and women 11% (277/2426) of LGV tests (Table 1 ). Overall, LGV prevalence was 15% (366/2426), and was highest among HIV-positive MSM (33%; 230/692) and lowest in women (0.4%; 1/277). MSM accounted for 93% (342/366) of all positive samples, and 67% (230/342) of MSM with LGV were HIV-positive. In 2014, there were 3, 434 CT diagnoses reported by GUM clinics in HIV-positive MSM, but we found only 692 HIV positive MSM had a CT sample tested for LGV, while 1, 639 CT samples were from MSM without HIV, heterosexual men, or women, suggesting inadequate testing of CT samples from HIV-positive MSM. Conclusion: Although miscoding in GUMCADv2 may partially explain some LGV testing in heterosexual men and women and HIV negative MSM, these data still suggest that LGV testing might be targeted more effectively to conserve resources and maximise identification of LGV.